2016
DOI: 10.1038/srep31703
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and anti-hyperglycemic efficacy of various tea types in mice

Abstract: Tea, a beverage consumed worldwide, has proven anti-hyperglycemic effects in animal models. Better efficacies of tea beverages are frequently associated with high-dose levels, whose safety attracts considerable attention. Based on the inherent nature of tea catechin oxidation, fresh tea leaves are manufactured into diverse tea types by modulating the oxidation degree of catechins. The present study aimed to assess various tea types for their safety properties and anti-hyperglycemic effects. Mice were allowed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Ortsäter et al [ 21 ] reported that, in db/db mice, EGCG reduced the pathological changes of islets and increased the number and size of islet cells, thus accordingly improving the function of pancreatic secretion, which helped to delay the course of metabolic syndrome. However, it has been proven that high doses of EGCG produced cytotoxicity and hepatotoxicity, which indicates that crude extracts might be safer than a single substance [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ortsäter et al [ 21 ] reported that, in db/db mice, EGCG reduced the pathological changes of islets and increased the number and size of islet cells, thus accordingly improving the function of pancreatic secretion, which helped to delay the course of metabolic syndrome. However, it has been proven that high doses of EGCG produced cytotoxicity and hepatotoxicity, which indicates that crude extracts might be safer than a single substance [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large yellow tea, made from “one bud 6 leaves” of tea plant ( Camellia sinensis) , is one of the most famous traditional yellow teas in China, which is very popular because of its unique burnt flavor. A recent study from the Institute of Cancer Research (ICR) proved that yellow tea had a significant anti-hyperglycemic effect in high-fat-diet-induced mice when compared with green tea, black tea, and dark tea, which confirmed that yellow tea had a certain role in the recovery of glucose metabolism disorder [ 22 ]. However, high-fat-diet-induced ICR mice are not typical diabetic mice, and there is a lack of long-term experiments investigating the effect of yellow tea on rodent models of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al declared that TPS treatment could alleviate insulin resistance and decrease blood glucose in diabetic mice, which might be mediated by the regulation of the PI3K/Akt signal pathway as revealed by the up-regulated expression of PI3Kp85/p-Akt/GLUT4-signaling molecules [147]. Additionally, various kinds of tea might have different anti-hyperglycemic strength, and yellow tea might be a better choice compared to green and black teas [148]. In another study, mixtures of dried green tea leaves and Aquilariae lignum powder at weight ratio of 49:1 were wet-fermented for 12 h at 60 • C and steamed for 30 s at 100 • C after being dried for 1 week at 15 • C, then the steamed mixtures were cooled and additionally dried at 15 • C for 3 days [149].…”
Section: Anti-diabetic Effect In Vivomentioning
confidence: 99%
“…Consumption of tea has been reported with few adverse events [127,148,236]. Tumorigenic, mutagenic, teratogenic, and sub-chronic toxicity of tea-related ingredients have not been observed in animal experiments and human studies, and the no-observed-adverse-effect level (NOAEL), observed safety level, and tolerable upper intake level were far from the functional doses [26,222,223,237].…”
Section: Potential Safety Issuesmentioning
confidence: 99%
“…Tea is a worldwide consumed beverage and the green one is broadly used as a functional beverage and dietary antioxidant supplement as it contains more catechins, a potent antioxidant than the other type of Camellia sinensis tea (Tsai et al 2013). In addition, tea has demonstrated anti-hyperglycemic properties (in animal models) but its efficacies are associated with high-dose levels (Han et al 2016). Polyphenols are known to contribute to the dietary antioxidant upon consumption of fruits, herbs, and spices, which can be found in the tonic formulation and tea.…”
Section: Introductionmentioning
confidence: 99%